TEMATIK DALAM ANTOLOGI PUISI “SEUNTAI HARAP” KARYA PESERTA DIDIK SMA NEGERI 8 DENPASAR - I.G.A.D.C. Rasmi (Widyadari, 2025)
This study aims to (1) analyze the major theme elements in the poetry anthology "Seuntai Harapan" by students of SMA Negeri 8 Denpasar and (2) analyze minor themes in the poetry anthology "Seuntai Harapan" by students at SMA Negeri 8 Denpasar. This research is based on theory, literary appreciation, poetry, intrinsic and extrinsic elements. The research subject is poetry book and the thematic research object. The research method used is descriptive qualitative. Data collection is done by library or documentation method. In general, the poetry anthology "Seuntai Harapan" by students of SMA Negeri 8 Denpasar carries the theme of love with various twists and turns. The spices of falling in love, separation, pain, loss, courage, sincerity become a coherent whole in this anthology of poetry. The results of the research from ten analyzed poems, found major themes namely longing, loss, independence, and love. Of the ten poems whose analysis of minor themes were found, steadfastness, steadfastness, persistent, hardworking, diligent, tenacious, hero, courageous, and diligent.